Sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin as well as preparation method and application thereof

The sulfonic acid-containing structure hydroxymethyl self-crosslinking cation exchange resin is prepared through solution polymerization-hydroxyl self-crosslinking reaction, which solves the problem of low ion exchange capacity of existing resins, achieves high ion exchange capacity and strong ion exchange capacity, and expands its application potential in many fields.

CN119613604AActive Publication Date: 2025-03-14SHANDONG XINGSHUN NEW MATERIAL JOINT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510020092.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-14
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing cation exchange resins containing sulfonic acid group structure have low ion exchange capacity and insufficient ion exchange capacity.

Method used

The sulfonic acid structure hydroxymethyl self-crosslinking type cation exchange resin is prepared by a one-step reaction of solution polymerization-hydroxyl self-crosslinking, and the degree of sulfonation and crosslinking are controlled to regulate the ion exchange capacity.

Benefits of technology

The ion exchange capacity of cation exchange resin has been improved and its ion exchange capacity has been enhanced, making it more potential application value in water treatment, new energy battery electrolytes, natural drug purification and petroleum mining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613604A_ABST
    Figure CN119613604A_ABST
Patent Text Reader

Abstract

The invention provides hydroxymethyl self-crosslinking cation exchange resin containing a sulfonic acid structure as well as a preparation method and application of the hydroxymethyl self-crosslinking cation exchange resin, and relates to the technical field of cation exchange resin. The sulfonation degree is regulated and controlled by controlling the content of the sulfonic acid-containing structural unit, and the crosslinking degree is regulated and controlled by controlling the content of the hydroxymethyl-containing structural unit, so that the ion exchange capacity is regulated and controlled. The hydroxymethyl self-crosslinking cation exchange resin containing the sulfonic acid structure is high in ion exchange capacity and has important potential application value in the fields of water treatment, new energy battery electrolyte, natural medicine purification, oil exploitation and the like. The hydroxyl self-crosslinking cation exchange resin containing the sulfonic acid structure can be prepared through a one-step reaction, concentrated sulfuric acid is not needed for sulfonation, compared with a traditional concentrated sulfuric acid sulfonation process, the preparation process is simpler, more convenient and safer, reaction conditions are milder and more environmentally friendly, the product yield is high, separation is easy, the production cost is low, and the method is suitable for industrial production. The method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cation exchange resins, and in particular to a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin and a preparation method and application thereof. Background Art

[0002] Cationic exchange resins containing sulfonic acid group structures are an important type of functional polymer materials. They are widely used in water treatment and are key core materials for the preparation of ultrapure water and drinking pure water. Cationic exchange resins containing sulfonic acid group structures can also be used as solid gel electrolytes in new energy lithium-ion batteries to further improve battery efficiency and safety. In addition, cationic exchange resins containing sulfonic acid group structures also have important application value in the fields of natural drug separation, food purification, and oil extraction. The existing cationic exchange resins containing sulfonic acid group structures have low ion exchange capacity and are not good enough. Therefore, the development of cationic exchange resins with high ion exchange capacity containing sulfonic acid group structures has important academic research and practical application value. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin and its preparation method and application. The sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin provided by the present invention has a high ion exchange capacity.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin having a structure shown in Formula I:

[0006]

[0007] Wherein, based on the total amount of x, y and z being 100 mol %, the total amount of x is 25 to 40 mol % and the total amount of y is 10 to 25 mol %.

[0008] The present invention also provides a method for preparing the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin described in the above technical solution, comprising the following steps:

[0009] Mixing monomers, initiators and organic solvents to carry out solution polymerization-hydroxyl self-crosslinking reaction to obtain the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin;

[0010] The monomers are 2-acrylamide-2-methylpropanesulfonic acid, N-hydroxymethyl acrylamide and methyl methacrylate, wherein the content of 2-acrylamide-2-methylpropanesulfonic acid in the monomers is 25-40 mol %, and the content of N-hydroxymethyl acrylamide is 10-25 mol %.

[0011] Preferably, the amount of the initiator is 0.2-1% of the total amount of the monomers.

[0012] Preferably, the initiator comprises at least one of dibenzoyl peroxide and azobisisobutyronitrile.

[0013] Preferably, the organic solvent includes at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.

[0014] Preferably, the mass of the organic solvent is 2 to 6 times the total mass of the monomers.

[0015] Preferably, the temperature of the solution polymerization-hydroxyl self-crosslinking reaction is 70-90° C. and the time is 1-2 hours.

[0016] Preferably, after the solution polymerization-hydroxyl self-crosslinking reaction, the method further comprises: sequentially crushing, washing and drying the self-crosslinking gel polymer obtained by the solution polymerization-hydroxyl self-crosslinking reaction.

[0017] Preferably, the washing detergent comprises at least one of ethanol and methanol.

[0018] The present invention also provides the use of the self-crosslinking cation exchange resin containing sulfonic acid structure hydroxymethyl described in the above technical scheme or the self-crosslinking cation exchange resin containing sulfonic acid structure hydroxymethyl obtained by the preparation method described in the above technical scheme in environmental water treatment, new energy battery electrolytes, natural medicine purification or oil extraction.

[0019] The present invention regulates the sulfonation degree by controlling the content (x value) of the sulfonic acid structural unit, and regulates the crosslinking degree by controlling the content (y value) of the hydroxymethyl structural unit, thereby realizing the regulation of the ion exchange capacity. The sulfonic acid structure hydroxymethyl self-crosslinking cation exchange resin provided by the present invention, wherein the total amount of x is 25-40 mol%, and the total amount of y is 10-25 mol%, has a high ion exchange capacity, and has important potential application value in the fields of water treatment, new energy battery electrolytes, natural medicine purification, and oil extraction.

[0020] The sulfonic acid structure hydroxyl self-crosslinking type cation exchange resin provided by the present invention can be obtained by solution polymerization-hydroxyl self-crosslinking one-step reaction preparation, and it is not necessary to use concentrated sulfuric acid for sulfonation, and the preparation process is simpler and safer than the traditional concentrated sulfuric acid sulfonation process, and the reaction conditions are also more gentle and environmentally friendly, and the product yield is high, and it is easy to separate, and the production cost is low, and it is suitable for industrial production. Moreover, the present invention can control the sulfonation degree and crosslinking degree of the hydroxymethyl self-crosslinking type cation exchange resin containing sulfonic acid structure by monomer ratio, wherein the sulfonation degree is regulated by 2-acrylamide-2-methylpropanesulfonic acid dosage ratio, and the crosslinking degree can be regulated by N-hydroxymethyl acrylamide dosage ratio, thereby realizing the regulation of the ion exchange capacity of the cation exchange resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the infrared spectrum of the hydroxymethyl self-crosslinking cation exchange resin containing sulfonic acid structure in Example 1;

[0022] Figure 2 is the infrared spectrum of the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin in Example 2;

[0023] Figure 3 This is the infrared spectrum of the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin in Example 3. DETAILED DESCRIPTION

[0024] The present invention provides a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin having a structure shown in Formula I:

[0025]

[0026] Wherein, based on the total amount of x, y and z being 100 mol %, the total amount of x is 25 to 40 mol % and the total amount of y is 10 to 25 mol %.

[0027] In a specific embodiment of the present invention, based on the total amount of x, y and z as 100 mol%, the total amount of x can be 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol% or 40 mol%.

[0028] In a specific embodiment of the present invention, based on the total amount of x, y and z as 100 mol%, the total amount of y can be 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%.

[0029] The present invention regulates the sulfonation degree by controlling the content (x value) of the sulfonic acid structural unit, and regulates the crosslinking degree by controlling the content (y value) of the hydroxymethyl structural unit, thereby realizing the regulation of the ion exchange capacity. The sulfonic acid structure hydroxymethyl self-crosslinking cation exchange resin provided by the present invention, wherein the total amount of x is 25 to 40 mol%, and the total amount of y is 10 to 25 mol%, has a high ion exchange capacity, and has important potential application value in the fields of water treatment, new energy battery electrolytes, natural medicine purification, and oil extraction.

[0030] The present invention also provides a method for preparing the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin described in the above technical solution, comprising the following steps:

[0031] Mixing monomers, initiators and organic solvents to carry out solution polymerization-hydroxyl self-crosslinking reaction to obtain the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin;

[0032] The monomers are 2-acrylamide-2-methylpropanesulfonic acid, N-hydroxymethyl acrylamide and methyl methacrylate, wherein the content of 2-acrylamide-2-methylpropanesulfonic acid in the monomers is 25-40 mol %, and the content of N-hydroxymethyl acrylamide is 10-25 mol %.

[0033] In the present invention, the preparation route of the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin is as follows:

[0034]

[0035] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0036] In the present invention, the initiator preferably includes at least one of dibenzoyl peroxide and azobisisobutyronitrile. In the present invention, the amount of the initiator is preferably 0.2-1% of the total amount of monomers, and in specific embodiments, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.

[0037] In the present invention, the organic solvent preferably includes at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone. In the present invention, the mass of the organic solvent is preferably 2 to 6 times the total mass of the monomers, and in specific embodiments, it can be 2 times, 2.5 times, 3 times, 3.5 times, 4 times, 4.5 times, 5 times, 5.5 times or 6 times.

[0038] In the present invention, the temperature of the solution polymerization-hydroxyl self-crosslinking reaction is preferably 70-90°C, and in specific embodiments it can be 70°C, 75°C, 80°C, 85°C or 90°C; the time of the solution polymerization-hydroxyl self-crosslinking reaction is preferably 1-2h, and in specific embodiments it can be 1h, 1.5h or 2h.

[0039] In the present invention, after the solution polymerization-hydroxyl self-crosslinking reaction, it is preferred that the self-crosslinking gel polymer obtained by the solution polymerization-hydroxyl self-crosslinking reaction is crushed, washed and dried in sequence. In the present invention, the washing detergent preferably includes at least one of ethanol and methanol; the mass of the detergent is preferably 5 to 10 times the total mass of the monomer, and in a specific embodiment it can be 5 times, 6 times, 7 times, 8 times, 9 times or 10 times. In the present invention, the drying temperature is preferably 100 to 180°C, and in a specific embodiment it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C; the drying time is preferably 12 to 24h, and in a specific embodiment it can be 12h, 15h, 18h, 20h, 22h or 24h.

[0040] The existing preparation of cationic exchange resins containing sulfonic acid group structures is mainly to first prepare cross-linked polystyrene white balls through suspension copolymerization of styrene and divinylbenzene, and then introduce sulfonic acid groups through concentrated sulfuric acid sulfonation reaction at a relatively high temperature. A large amount of highly corrosive sulfuric acid is required in the preparation process, and the safety and environmental protection pressure is relatively large; and the sulfonation reaction after concentrated sulfuric acid is usually difficult to complete, the prepared ion exchange resin has a low degree of sulfonation, a low ion exchange capacity of the resin, and a weak ion exchange capacity. The hydroxyl self-crosslinking cationic exchange resin containing sulfonic acid structure provided by the present invention is prepared by solution polymerization-hydroxyl self-crosslinking one-step reaction, does not need to be sulfonated using concentrated sulfuric acid, the preparation process is simpler and safer than the traditional concentrated sulfuric acid sulfonation process, the reaction conditions are also milder and more environmentally friendly, the product yield is high, and it is easy to separate, the production cost is low, and it is suitable for industrial production. Moreover, the present invention can control the sulfonation degree and cross-linking degree of the hydroxymethyl self-cross-linking cation exchange resin containing a sulfonic acid structure through the monomer ratio, wherein the sulfonation degree is regulated by the dosage ratio of 2-acrylamide-2-methylpropanesulfonic acid, and the cross-linking degree is regulated by the dosage ratio of N-hydroxymethyl acrylamide, thereby realizing the regulation of the ion exchange capacity of the cation exchange resin.

[0041] The present invention also provides the use of the sulfonic acid structure hydroxymethyl self-crosslinking cation exchange resin described in the above technical solution or the sulfonic acid structure hydroxymethyl self-crosslinking cation exchange resin prepared by the preparation method described in the above technical solution in environmental water treatment, new energy battery electrolyte, natural medicine purification or oil production. The present invention regulates the sulfonation degree by the content (x value) of the sulfonic acid structure unit, and regulates the crosslinking degree by controlling the content (y value) of the hydroxymethyl structure unit, thereby realizing the regulation of the ion exchange capacity. The ion exchange capacity of the sulfonic acid structure hydroxymethyl self-crosslinking cation exchange resin provided by the present invention is high, and it has important potential application value in the fields of water treatment, new energy battery electrolyte, natural medicine purification, oil production, etc.

[0042] To further illustrate the present invention, the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0043] The raw materials and drugs used in the examples are as follows: 2-acrylamido-2-methylpropanesulfonic acid (purity 99%), N-hydroxymethyl acrylamide (purity 99%) and methyl methacrylate (purity 99%) were purchased from Anaiji Chemical Reagent Co., Ltd.; dibenzoyl peroxide (purity 99%) and azobisisobutyronitrile (purity 99%) were purchased from Shanghai Aladdin Reagent Co., Ltd.; N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., chemically pure. The ion exchange capacity of the cation exchange resin was tested using the GB 8144-1987 standard method for determining the exchange capacity of cation exchange resins.

[0044] Example 1

[0045] 2.0724 g (0.01 mol) of 2-acrylamido-2-methylpropanesulfonic acid, 1.011 g (0.01 mol) of N-hydroxymethyl acrylamide (purity 99%) and 2.0024 g (0.02 mol) of methyl methacrylate were respectively added to a dry three-necked flask equipped with a mechanical stirrer and a condenser, 12 mL of N-methylpyrrolidone and 0.02 g of dibenzoyl peroxide were added, the temperature was raised to 90° C. and stirred for reaction for 1 h to obtain a self-crosslinking gel polymer, the self-crosslinking gel polymer was crushed, the product was washed with 60 mL of ethanol in portions, and dried at 180° C. for 12 h to obtain a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin with a yield of 95% and an ion exchange capacity test value of 1.961 meq / g.

[0046] Figure 1This is the infrared spectrum of the hydroxymethyl self-crosslinking cation exchange resin containing sulfonic acid structure. -1 The broad absorption peak at 1151 cm -1 、1041cm -1 and 624cm -1 It is the characteristic absorption peak of sulfonic acid, 2900~3100cm -1 The absorption peak at 1732 cm is the characteristic absorption peak of alkyl group. -1 and 1670cm -1 The absorption peaks at 1226 cm -1 The absorption peak at is the cross-linked ether bond absorption peak.

[0047] Example 2

[0048] 3.1086 g (0.015 mol) of 2-acrylamido-2-methylpropanesulfonic acid, 1.011 g (0.01 mol) of N-hydroxymethylacrylamide (purity 99%) and 2.0024 g (0.02 mol) of methyl methacrylate were respectively added to a dry three-necked flask equipped with a mechanical stirrer and a condenser, 18 mL of N,N-dimethylacetamide and 0.04 g of dibenzoyl peroxide were added, the temperature was raised to 70° C. and stirred for reaction for 2 h to obtain a self-crosslinking gel polymer, the self-crosslinking gel polymer was crushed, the product was washed with 90 mL of methanol in portions, and dried at 100° C. for 24 h to obtain a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin, the yield was 96%, and the ion exchange capacity test value was 2.451 meq / g.

[0049] Figure 2 This is the infrared spectrum of the hydroxymethyl self-crosslinking cation exchange resin containing sulfonic acid structure. -1 The broad absorption peak at 1151 cm -1 、1041cm -1 and 624cm -1 It is the characteristic absorption peak of sulfonic acid, 2900~3100cm -1 The absorption peak at 1731cm is the characteristic absorption peak of alkyl group. -1 and 1670cm -1 The absorption peaks at 1220 cm-1 are the characteristic absorption peaks of ester group and amide group. -1 The absorption peak at is the cross-linked ether bond absorption peak.

[0050] Example 3

[0051] 4.1448 g (0.02 mol) of 2-acrylamido-2-methylpropanesulfonic acid, 1.011 g (0.01 mol) of N-hydroxymethylacrylamide (purity 99%) and 2.0024 g (0.02 mol) of methyl methacrylate were respectively added to a dry three-necked flask equipped with a mechanical stirrer and a condenser, 20 mL of N,N-dimethylformamide and 0.065 g of azobisisobutyronitrile were added, the temperature was raised to 80° C. and stirred for reaction for 1.5 h to obtain a self-crosslinking gel polymer, the self-crosslinking gel polymer was crushed, the product was washed with 120 mL of ethanol in portions, and dried at 140° C. for 18 h to obtain a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin with a yield of 95% and an ion exchange capacity test value of 2.793 meq / g.

[0052] Figure 3 This is the infrared spectrum of the hydroxymethyl self-crosslinking cation exchange resin containing sulfonic acid structure. -1 The broad absorption peak at 1157 cm -1 、1040cm -1 and 629cm -1 It is the characteristic absorption peak of sulfonic acid, 2900~3100cm -1 The absorption peak at 1731cm is the characteristic absorption peak of alkyl group. -1 and 1677cm -1 The absorption peaks at 1219 cm -1 The absorption peak at is the cross-linked ether bond absorption peak.

[0053] Example 4

[0054] 2.0724 g (0.01 mol) of 2-acrylamido-2-methylpropanesulfonic acid, 0.5055 g (0.005 mol) of N-hydroxymethyl acrylamide (purity 99%) and 2.0024 g (0.02 mol) of methyl methacrylate were respectively added to a dry three-necked flask equipped with a mechanical stirrer and a condenser, 15 mL of N-methylpyrrolidone and 0.035 g of dibenzoyl peroxide were added, the temperature was raised to 85° C. and stirred for reaction for 1 h to obtain a self-crosslinking gel polymer, the self-crosslinking gel polymer was crushed, the product was washed with 70 mL of ethanol in portions, and dried at 120° C. for 16 h to obtain a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin with a yield of 95% and an ion exchange capacity test value of 2.183 meq / g.

[0055] Example 5

[0056] 4.1448 g (0.02 mol) of 2-acrylamido-2-methylpropanesulfonic acid, 0.5055 g (0.05 mol) of N-hydroxymethyl acrylamide (purity 99%) and 2.503 g (0.025 mol) of methyl methacrylate were respectively added to a dry three-necked flask equipped with a mechanical stirrer and a condenser, 30 mL of N,N-dimethylformamide and 0.09 g of azobisisobutyronitrile were added, the temperature was raised to 75° C. and stirred for reaction for 1.5 h to obtain a self-crosslinking gel polymer, the self-crosslinking gel polymer was crushed, the product was washed with 200 mL of ethanol in batches, and dried at 140° C. for 14 h to obtain a sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin with a yield of 94% and an ion exchange capacity test value of 2.796 meq / g.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin having a structure shown in Formula I: in, Based on the total amount of x, y and z being 100 mol%, the total amount of x is 25 to 40 mol% and the total amount of y is 10 to 25 mol%.

2. The method for preparing the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin according to claim 1, characterized in that: The following steps are involved: Mixing monomers, initiators and organic solvents to carry out solution polymerization-hydroxyl self-crosslinking reaction to obtain the sulfonic acid structure-containing hydroxymethyl self-crosslinking cation exchange resin; The monomers are 2-acrylamide-2-methylpropanesulfonic acid, N-hydroxymethyl acrylamide and methyl methacrylate, wherein the content of 2-acrylamide-2-methylpropanesulfonic acid in the monomers is 25-40 mol %, and the content of N-hydroxymethyl acrylamide is 10-25 mol %.

3. The preparation method according to claim 2, characterized in that: The amount of the initiator is 0.2-1% of the total amount of the monomers.

4. The preparation method according to claim 2 or 3, characterized in that: The initiator includes at least one of dibenzoyl peroxide and azobisisobutyronitrile.

5. The preparation method according to claim 2, characterized in that: The organic solvent includes at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.

6. The preparation method according to claim 2 or 5, characterized in that: The mass of the organic solvent is 2 to 6 times the total mass of the monomers.

7. The preparation method according to claim 2, 3 or 5, characterized in that: The temperature of the solution polymerization-hydroxyl self-crosslinking reaction is 70-90° C. and the time is 1-2 hours.

8. The preparation method according to claim 7, characterized in that: After the solution polymerization-hydroxyl self-crosslinking reaction, the method further comprises: sequentially crushing, washing and drying the self-crosslinking gel polymer obtained by the solution polymerization-hydroxyl self-crosslinking reaction.

9. The preparation method according to claim 8, characterized in that: The washing detergent includes at least one of ethanol and methanol.

10. Use of the self-crosslinking cation exchange resin containing hydroxymethyl groups with sulfonic acid structure according to claim 1 or the self-crosslinking cation exchange resin containing hydroxymethyl groups with sulfonic acid structure obtained by the preparation method according to any one of claims 2 to 9 in environmental water treatment, new energy battery electrolytes, natural medicine purification or oil extraction.

Citation Information

Patent Citations

  • Strong-acid cation exchange resin and preparing method thereof

    CN104119467A

  • Anode water-based adhesive capable of improving discharge platform of lithium ion battery and preparation method of anode water-based adhesive

    CN116936807A

  • Macroporous ion exchange resins

    US20050261385A1